Impact of molar incisor hypomineralization on oral health-related quality of life, dental fear and anxiety in Swedish children - Adnan Hajdarević; Birgitta Jälevik; Emina Čirgić; Agneta Robertson; Nina Sabel (Acta Odontologica Scandinavica)
Objectives: The aims this research were to analyze self-reported oral health-related quality of life (OHRQoL) and dental fear and anxiety (DFA) in 11-year-old patients after either restorative treatment or after extraction of first permanent molars (FPM) affected by severe molar incisor hypomineralization (MIH). The research question focused on whether these treatments lead to different outcomes of DFA and OHRQoL over time.